(untitled) (Jurnal Bahasa, 2001)
The aim of this research is to identify the attitude and interest of the non-Malay pupils and its relationship with family, teacher, teaching aids, and school factors. Questionnaires involving 300 pupils were used in schools in Negeri Sembilan. It was revealed that the non-Malay pupils faced problems in the learning of Bahasa Melayu in schools. However, the attitude and interest of these pupils towards the learning of Bahasa Melayu is not significant to the family, teacher, teaching aids, and school factors.